2022
DOI: 10.1093/nar/gkac945
|View full text |Cite
|
Sign up to set email alerts
|

RM2Target: a comprehensive database for targets of writers, erasers and readers of RNA modifications

Abstract: RNA modification is a dynamic and reversible process regulated by a series of writers, erasers and readers (WERs). Abnormal changes of WERs will disrupt the RNA modification homeostasis of their target genes, leading to the dysregulation of RNA metabolisms such as RNA stability and translation, and consequently to diseases such as cancer. A public repository hosting the regulatory relationships between WERs and their target genes will help in understanding the roles of RNA modifications in various physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 71 publications
(78 reference statements)
1
24
0
Order By: Relevance
“…We firstly used the RM2Target platform ( http://rm2target.canceromics.org/ ) to predict the m 6 A modification role of LRPPRC in PD-L1 ( 23 ). Our prediction data demonstrated that PD-L1 might be potentially modified by LRPPRC-mediated m 6 A modification.…”
Section: Resultsmentioning
confidence: 99%
“…We firstly used the RM2Target platform ( http://rm2target.canceromics.org/ ) to predict the m 6 A modification role of LRPPRC in PD-L1 ( 23 ). Our prediction data demonstrated that PD-L1 might be potentially modified by LRPPRC-mediated m 6 A modification.…”
Section: Resultsmentioning
confidence: 99%
“…The following are the emerged databases of methylation modifications associated with some specific diseases and fields: (1) After m6A methylation-related genes based on The Cancer Genome Atlas (TCGA) were used to predict the prognosis of hepatocellular carcinoma ( Group et al, 2020 ; Liu et al, 2020b ; Li et al, 2021b ), cancer-related methylation modification databases have begun to emerge, including, Lnc2Cancer 3.0 and OncoDB ( Gao et al, 2021 ; Tang et al, 2022 ); (2) Osteoarthritis-omics and molecular biomarkers (OAOB), which are a group of database containing differential molecular biomarkers related to osteoarthritis ( Li et al, 2022a ); (3) Other than disease, Pan et al (2022) established an integrative multi-omic database (iMOMdb) of Asian pregnant women providing the first blood-based multi-omic analysis of pregnant women in Asia. This database contains high-resolution genotypes, DNA methylation, and transcriptome profiles, and fills the knowledge gap of complex traits in populations of Asian ancestry; (4) Gao et al (2022) developed AgingBank, an experimentally supported multiomics database of information related to aging in multiple species; (5) ProMetheusDB, a database generated by analyzing and sorting cell culture experiments data using ML tools from the protein perspective ( Massignani et al, 2022 ); (6) compendium of protein lysine modifications (CPLM 4.0), a post-translational modification (PTMs) database ( Zhang et al, 2022 ); (7) tRNA-related databases containing high-throughput tRNA sequencing data ( Sajek et al, 2020 ); (8) RNAWRE and RM2 Target are two databases focusing on information of writers, readers, and erasers ( Nie et al, 2020 ; Bao et al, 2022 ); and (9) SyStemCell, a multiple-levels experimental database for stem cell research ( Yu et al, 2012 ). With the emergence of these specialized and multi-angle RNA methylation related databases, the traditional databases are also constantly updated and developed.…”
Section: Methods To Detect Rna Modificationsmentioning
confidence: 99%
“…• RMDisease V2.0 (Song et al, 2022b), AgingBank (Gao et al, 2022), CPLM 4.0 (Zhang et al, 2022), OncoDB (Tang et al, 2022), ASMdb (Zhou et al, 2022), iMOMdb (Pan et al, 2022), OAOB (Li et al, 2022a), ProMetheusDB (Massignani et al, 2022), RM2Target (Bao et al, 2022(Bao et al, ) (2022 performance based on its SpinalNet architecture that was inspired by the human somatosensory system.…”
Section: Targets Of Rna Methylation/ Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…tModBase ( 8 ) focuses on modifications of tRNA, their dynamics and biomedical implications, and the enzymes involved. RM2Target ( 9 ), a development of the earlier m6A2Target database ( 10 ), covers writes, erasers and readers of nine RNA modifications as well as diverse annotations and biomedical implications. The third of the trio, DirectRMDB ( 11 ), collects data from direct RNA sequencing that captures quantitative RNA modifications, annotating the results in an isoform-specific manner.…”
Section: New and Updated Databasesmentioning
confidence: 99%